(untitled) (Journal of Educational Sciences, 2016)
This article defines the problems of research competencies formation of the future teachers. An analysis of the theoretical research basis allowed to the authors to introduce the concept of “research competence of the teacher” as a characteristic of the personality, that means the possession of skills and methods of the research in searching knowledge for solving educational problems, constructing the whole pedagogical process within the requirements of the modern education. The authors say, there is a strong need for preparing specialists in higher education, who possesses research competencies, as the realities of the society demands creative and thinking unconventionally specialists, able to find creative decisions of pedagogical problems. The article presents the characteristics of scientific, instrumental and professional research competencies of the future teachers in primary school, also it defines the way of their formation, both during the process of giving classes and during the process of all types of pedagogical practice at school. The main part in formation of research competencies of the future teachers in primary school, the authors give attention to pedagogical practice, as in the process of organizing the lesson, students make their own investigations in education and educational process of the learners, make diagnosis of intellectual development of pupils, carry out experimental works on formation of moral qualities of the child’s personality. It is essential part in the process of research if the students strive to improve the learning process and educational process of pupils.